COAXIM, an innovative protocol for mass clonal propagation of coconuts - Panis, Bart; Wilms, Hannes; Liao, Yu-chun; Moreira, Suzana (2023)
1st International Scientific Conference on Coconut Research and Development 27-30 November 2023 - Los Banos, Laguna, Philippines ( Hybrid )